Evaluation of design parameters on the outcome of intrastromal ring surgery using biomechanical simulations. - Shima Bahramizadeh-Sajadi; Hamid Reza Katoozian; Miguel Angel Ariza-Gracia; Morteza Gholami; Alireza Baradaran-Rafii; Philippe Büchler (PLoS ONE)
Background The cornea plays a role in the refractive power of the eye, and when its natural curvature and thickness are compromised by diseases such as keratoconus or high myopia, this results in loss of visual acuity. Intracorneal rings (ICRs) were developed as a treatment option to restore the natural corneal curvature by implanting rings into tunnels cut within the corneal stroma. However, selecting and placing the appropriate ring can be difficult, and predicting refractive outcomes is challenging. Objective The purpose of this study was to better understand the design parameters of the rings that determine postoperative refractive and mechanical outcomes. Methods We developed an automated finite element simulation pipeline for ICR implantation and tested 300 variations of 20 ICRs. Results The outcome of ICR was dominated by the vertical size of the ring; 84% of the change in corneal curvature can be attributed to the vertical size of the ring, while only 13% were attributed to the detailed cross-sectional shape of the ring. However, the cross-sectional shape of the ring is limited to the change in axial length and contact pressure between the ring and the cornea. The horizontal dimension of the ring plays only a minor role in the postoperative outcome. Conclusion These results support Keraring's approach to ring scaling, in which only the vertical dimension of the ring is changed, while the horizontal dimension remains constant. Numerical models help to understand ICR outcomes, design implants, and personalize empirical nomograms to achieve more successful postoperative outcomes.